Foot and Ankle Patient Education Materials and Artificial Intelligence Chatbots: A Comparative Analysis - Aarav S. Parekh; Joseph A.S McCahon DO; Amy Nghe BA; David I. Pedowitz DO; Joseph N. Daniel DO; Selene G. Parekh MD, MBA (Foot & Ankle Orthopaedics)
Category: Other; Sports Introduction/Purpose: On its current trajectory, AI chatbots may become the primary source of information for patient education material in the field of orthopaedics. Despite this, there has been no evaluation of the accuracy and validity of foot and ankle patient education material generated by AI platforms. The purpose of this study was to perform a comparative analysis of foot and ankle patient education material generated by the ai chatbots, as they compare to the AOFAS recommended patient education website, footcaremd.org. Methods: ChatGPT, Google Bard, and Bing AI were used to generate patient educational materials on ten of the most common foot and ankle conditions. The content from these ai language model platforms was analyzed and compared with footcaremd.org for accuracy of included information. Accuracy was determined for each of the ten conditions on a basis of included information regarding background, symptoms, causes, diagnosis, treatments, surgical options, recovery procedures, and risks or preventions. Results: When compared to the reference standard of the AOFAS website: footcaremd.org, the AI language model platforms consistently scored below 60% in accuracy rates in all categories of the articles analyzed. ChatGPT was found to contain an average of 46.2% of key content across all included conditions when compared to footcaremd.org. Comparatively, Google Bard contained an average of 36.5% and Bing AI contained 28.0% of information included on footcaremd.org. Conclusion: AI language model generated patient education regarding common foot and ankle conditions provides limited content accuracy across all three AI chatbot platforms. Clinicians should be aware of the increasing popularity of these platforms and be prepared to answer questions or clarify misunderstandings, and when appropriate direct patients to more validated education material such as footcaremd.org.